Diabetes-induced biochemical changes in central and peripheral catecholaminergic systems - Gallego, M; Setién, R; Izquierdo, M J; Casis, O; Casis, E (Physiological research, 2003)
A great variety of alterations have been described in the nervous system of diabetic animals. They are named as diabetic neuropathy and affect the brain, spinal cord and peripheral nerves. In diabetic animals, plasma and tissue catecholamine levels have been reported to be increased, decreased or unchanged, and these disparities have been explained by differences in the tissues selected, severity or duration of diabetes. Dopamine, norepinephrine and epinephrine from different tissues were extracted by absorption onto alumina, and measured by high performance liquid chromatography with electrochemical detection. We found that diabetes alters catecholaminergic systems in a highly specific manner. The dopamine content is reduced in the dopaminergic nigrostriatal system only. Norepinephrine is differently altered in several areas of the sympathetic nervous system. It is increased in cardiac ventricles, and decreased in stellate ganglia and the blood serum. However, it is not altered in the central nervous system. Finally, epinephrine is only altered in the adrenal gland where it is increased, and in the serum where it is reduced. Our results suggest that diabetes reduces the activity of the nigrostriatal dopaminergic system. Changes found at the sympathoadrenal level could be explained by reduced norepinephrine and epinephrine synthesis, with increased storage due to a reduced release from synaptic vesicles.
Keywords: Catecholamines; Peripheral Nervous System; krevní glukóza; Medulla Oblongata; Adrenal Glands; mezencefalon; srdeční komory; Animals; nadledviny; Diabetes Mellitus, Experimental; Central Nervous System; Body Weight; adrenalin; Heart Ventricles; dopamin; ganglion stellatum; noradrenalin; bazální ganglia; Dopamine; Rats; Norepinephrine; pons; experimentální diabetes mellitus; Stellate Ganglion; sympatický nervový systém; medulla oblongata; Rats, Sprague-Dawley; tělesná hmotnost; potkani Sprague-Dawley; Pons; vysokoúčinná kapalinová chromatografie; zvířata; Sympathetic Nervous System; katecholaminy; krysa rodu Rattus; diabetické neuropatie; Blood Glucose; Chromatography, High Pressure Liquid; Diabetic Neuropathies; centrální nervový systém; Epinephrine; Mesencephalon; periferní nervový systém; Basal Ganglia